Role of Helicobacter Bacteria in Colitis and Colorectal Neoplasms: A Histopathological and Immunohistochemically Study - Mariam Riaz, Henna Khalid, (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Adenocarcinomas have progressed from hyper proliferative epithelium through adenomatous lesions to adenocarcinomas and adenomas. In this case, the adenomatous foci are typically neoplastic intraluminal protrusions and occasionally flat, dysplastic glandular growths, which are either filamentous or villous in nature, depending on the architectural position, etiologically, and genetic factors associated in their genesis. The present study aimed to evaluate the role of helicobacter bacteria in colitis and colorectal neoplasms. Methodology: This retrospective study included 60 patients’ samples collected of paraffin blocks at the Department of Pathology, WMC, Abbottabad and LRH Peshawar during the period from March 2020 to March 2022. Demographic details and clinical data taken from the pathology sheet included age, gender, tumor size, colorectal carcinoma site, distant metastasis presence, ulcerating, and fungating. A serial section of 5 mm thickness was cut from each block and mounted on a glass slide for histological evaluation. After staining with hematoxylin and eosin (H&E), a second section was mounted on charged slides for immune-histochemical evaluation. SPSS version 26 was used for data analysis. Results: Of the total 60 patients, there were 32 (53.3%) men and 38 (46.7%) women. The overall mean age was 46.8±3.46 years with age ranges from 20 years to 80 years. The distribution of patients were as follows: normal colon 15 (25%), colitis 15 (25%), colonic tubular adenoma 10 (16.7%), and colorectal carcinoma 20 (33.3%). Among 60 patients stained for anti-H. pyroli, the prevalence of positive and negative antibodies was 16 (26.7%) and 44 (73.3%) respectively. The incidence of negative and positive anti-H. Pylori antibodies in normal colon, colitis, colonic tubular adenoma, and colorectal carcinoma were as follows: 4 (26.7%) and 11 (73.3%), 5 (33.3%) and 10 (66.7%), 3 (30%) and 7 (70%), and 5 (25%) and 15 (75%) respectively. Out of 20 colorectal carcinoma, the incidence of sigmoid colon, rectum, transverse colon, and right colon was 9 (45%), 6 (30%), 3 (15%), and 2 (10%) respectively. The occurrence of lesion diameter <5 cm and >5 cm was 11 (55%) and 9 (45%) respectively. The prevalence of circumferential infiltrating type, ulcerative type, and fungating type was 12 (60%), 6 (30%), and 2 (10%) respectively. Based on colorectal cancer patients histological class, the incidence of adenocarcinomas, mucoid adenocarcinoma, and adenocarcinoma with neuroendocrine differentiation was 14 (70%), 3 (15%), and 3 (15%) respectively. Conclusion: The present study concluded that positive antibodies of H. pylori had no significant association with carcinoma, normal colon, tabular adenoma, and colitis. Still, determination of odd ratio (OR) estimating risk showed that adenoma (OR 2.0) and colitis (OR 1.39) had significant association with positivity of H. pylori. Additionally, Sigmoid colon was the most prevalent site followed by rectum, transverse colon, and right colon. Keywords: Helicobacter bacteria, Colitis, Carcinoma, Immunohistology